Gait Analysis in Orthopedic Foot and Ankle Surgery—Topical Review, Part 1: Principles and Uses of Gait Analysis. (January 2014) - Mayich, D. Joshua; Novak, Alison; Vena, Daniel; Daniels, Timothy R.; Brodsky, James W.
Gait analysis, the systematic study of human walking, is a field that has been studied for well over 100 years. With the technological and scientific advancements of the last several decades, there has been substantial improvement in our understanding of the mechanics of human walking. Particularly important has been the advancement in understanding of the differences between normal and pathological gait. The purpose of this paper is to review the principles of gait analysis, with a particular focus on the underlying methods and science. This will assist orthopedic foot and ankle surgeons in better understanding the methods and meaning of gait research and the publications that commonly appear in the orthopedic foot and ankle surgery literature. Level of Evidence: Level V, expert opinion.